Upaya Meningkatkan Kemampuan Bahasa Ekspresif Melalui Metode Bercerita Menggunakan Boneka Jari Tangan Pada Anak Usia Dini - Usep Dimyati; Esty Faatinisa; Taufik Maulana (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Expressive language skills are the ability to speak and write down information. Children's speaking skills can be developed by playing, because by playing children will get learning experiences that can improve their speaking and language skills. This research aims to improve children's expressive language skills. This type of research is Class Action Research (PTK) with research subjects for class B children, totaling 15 people. The research was carried out in 2 cycles every cycle of 2 meetings. Data was collected through observation, interviews, and documentation. Cycle I generally looks still low. After improvements were made by adding media, the second cycle increased to reach the desired percentage. It is concluded that the storytelling method using finger puppets can improve children's expressive language skills.